Evaluation of serum oxytocin levels in patients with depression, generalized anxiety disorder, panic disorder, and social anxiety disorder: A case-control study - Tuman, Taha Can; Yıldırım, Osman; Tufan, Ali Evren (Journal of Surgery and Medicine, 2021)
Background/Aim: Oxytocin, an endogenous anti-stress, antidepressant, and anxiolytic hormone, is reported to increase in stressful situations to reduce the hyperactivity of the hypothalamic-pituitary-adrenal (HPA) axis and amygdala for coping with stress and improving social functioning. This study aimed to compare serum oxytocin levels of patients with depression, generalized anxiety disorder (GAD), panic disorder (PD), and social anxiety disorder (SAD) with that of healthy controls. Methods: The study included 50 patients (25 male, 25 female) with major depression, 26 patients (9 male, 17 female) with GAD, 31 patients (14 male, 17 female) with SAD, and 40 patients (17 male, 23 female) with PD and 30 healthy volunteers. Hamilton Depression Rating Scale (HDRS), Hamilton Anxiety Rating Scale (HARS), Perceived Stress Scale (PSS), and Anxiety Sensitivity Index-3 (ASI-3) were applied to all groups. In addition, Generalized Anxiety Disorder-7 (GAD-7), Panic Disorder Severity Scale (PDSS), and Liebowitz Social Phobia Scale were applied to patients with GAD, panic disorder, and social anxiety disorder, respectively. Serum oxytocin levels were measured by ELISA. Results: Serum oxytocin levels of patients with depression were significantly lower, and those of patients with generalized anxiety disorder, social anxiety disorder, and panic disorder with agoraphobia were significantly higher compared to the control group (2.46 (2.8) vs. 2.86 (0.72), P=0.004, 11.49 (11.35) vs. 2.86 (0.72), P=0.001, 10.67 (11.32) vs. 2.86 (0.72), P=0.001, and 6.97 (5.01) vs. 2.86 (0.72), P=0.001, respectively). Conclusion: Lower oxytocin levels in depressed patients and higher oxytocin levels in patients with GAD, and PD with agoraphobia suggest that oxytocin has a role in psychiatric disorders. Further studies are needed to better understand the relationship between depression, anxiety disorders, oxytocin, and the underlying mechanisms.